Análise da estrutra dos canais de distribuição de produtos orgânicos em Fortaleza/CE - Oliveira, Rosangela Soares de (2011)
This research has as main objective to describe the operation of the Supply Chain of Organic Products (Fruits and Vegetables-processed and FLV) used in different forms of retail, specific objectives and establish a review into aspects related to the advantages and disadvantages of production, distribution and retail market for organic products. The study area is located in Fortaleza, in Ceará, which is characterized by an increasing demand for organic products, but we detected a lack of analysis on the structure of distribution channels. The methodology developed in this study is classified as exploratory, descriptive, qualitative multiple case studies. It was concluded that the market is with an acceptable degree of organization and development. The structures of the supply chain of organic products marketed differ according to the type of product sold (Fruits and Vegetables - FLV or processed) and the size of the establishment. Under the aspect of the structure of the distribution channel of products FLV is configured, the retailers surveyed, indirect channel marketing through short, while marketing the processed product is formed through an indirect channel for long. Finally, as to viability, it was concluded that the activity of marketing of organic products in Fortaleza is economically profitable and influences in the manufacture of products that guarantees citizenship, distributive justice, and Fair Trade (FT).